Triple Zero on Weakly Nearly Primary 2-Absorbing submodule - Hussen Hassan, Israa; Abdulla Salih, Marrwa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
In this paper, we introduce and investigate the concept of weakly nearly primary 2-absorbing triple zero submodule. A formal definition is proposed, and several theorems are established to describe the algebraic behavior of this type of submodule. The focus is placed on deriving theoretical results without the use of illustrative examples. Moreover, properties of weakly nearly primary 2-absorbing triple zero submodule are explored in relation to different module structures.